Activation of murine RAW264.7 macrophages by oligopeptides from sea cucumber (Apostichopus japonicus) and its molecular mechanisms. (December 2020) - Cai, Nan; Luo, Wenqi; Yao, Lijun; Li, Xiuting; Wang, Zuzhe; Xu, Hong; Li, Hui; Hu, Zhangli; Bao, Weiyang; Xu, Xu
Graphical abstract: Highlights: Small molecule oligopeptides extracted from sea cucumber ( Apostichopus japonicus ) (SCOP) were characterized. SCOP enhanced the immune activity of RAW264.7 macrophages as measured by the release of NO, TNF-α and IL-6. SCOP stimulated macrophages through the upregulation of the NF-κB and MAPK signaling pathways. Abstract: Sea cucumbers are valuable marine foods as well as a source of traditional medicines with various bioactivities. Macrophage activation by small-molecule oligopeptides obtained from the sea cucumber Apostichopus japonicus (SCOP) were investigated. After SCOP were proven nontoxic by oral administration and CCK-8 assays, we measured immune-stimulatory mRNA, pro-inflammatory cytokines, and NO production levels and determined the molecular mechanism of macrophage stimulation. Our results demonstrated that SCOP upregulated both the mRNA levels and the secretion of NO, TNF-α, and IL-6 in a dose-dependent manner. More importantly, SCOP contributed to the stimulation of macrophages through the upregulation of the NF-κB and MAPK signaling pathways. Taken together, these results indicated that SCOP exerted macrophage activation effects on RAW264.7 cells and that they could potentially be used as a functional food supplement in treating immune suppression.